2017
DOI: 10.1186/s12893-016-0202-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open nephroureterectomy to treat localized and/or locally advanced upper tract urothelial carcinoma: oncological outcomes from a multicenter study

Abstract: BackgroundMany studies have reported the oncological outcomes between open radical nephroureterectomy (ONU) and laparoscopic radical nephroureterectomy (LNU) of upper tract urothelial carcinoma (UTUC). However, few data have focused on the oncological outcomes of LNU in the subgroup of localized and/or locally advanced UTUC (T1–4/N0-X). The purpose of this study was to compare the oncological outcomes of LNU vs. ONU for the treatment in patients with T1–4/N0-X UTUC.MethodsWe collected and analyzed the data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Considerable efforts have been made to ensure the oncological outcomes equivalence between LNU and RANU. 5,7,14,15 No differences were noted in most studies, except in one meta-analysis that suggested a superiority of ONU for patients with locally advanced high-risk (pT3/ pT4 and/or high-grade) UTUC. 5 In consequence, MINU might represent an adequate alternative to ONU.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considerable efforts have been made to ensure the oncological outcomes equivalence between LNU and RANU. 5,7,14,15 No differences were noted in most studies, except in one meta-analysis that suggested a superiority of ONU for patients with locally advanced high-risk (pT3/ pT4 and/or high-grade) UTUC. 5 In consequence, MINU might represent an adequate alternative to ONU.…”
Section: Discussionmentioning
confidence: 98%
“…Minimally invasive surgery is currently widely used in urological oncology. Considerable efforts have been made to ensure the oncological outcomes equivalence between LNU and RANU . No differences were noted in most studies, except in one meta‐analysis that suggested a superiority of ONU for patients with locally advanced high‐risk (pT3/pT4 and/or high‐grade) UTUC .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to perform adequate lymphadenectomy does not seem to be influenced by the approach (open versus laparoscopic). In a comparative analysis of open versus laparoscopic nephroureterectomy, Liu et al found that 59.6% and 55.8% patients undergoing open and laparoscopic NU did not undergo a simultaneous lymphadenectomy respectively [21].…”
Section: Trends In Lymphadenectomymentioning
confidence: 99%
“…The main hurdle for lymphadenectomy during laparoscopy is the technical challenge associated with the procedure. There is a wide variability in the reported implementation of simultaneous lymphadenectomy during LNU (transperitoneal, retroperitoneal or hand assisted) [20,21,30]. During a minimally invasive approach, lymphadenectomy is performed predominantly for enlarged lymph nodes detected either on preoperative imaging or during surgery itself.…”
Section: Impact Of Minimally Invasive Surgery On Lymphadenectomymentioning
confidence: 99%
“…With the advancement of laparoscopic techniques and the accumulation of operative experience, laparoscopic total nephroureterectomy with excision of bladder cuff have been applicable to a growing number of pelvic ureteral cancer patients in many centers since it was successfully performed by Clayman et al in 1991[5,6]. Recently, laparoscopic nephroureterectomy has replaced open surgery as standard surgical treatment for upper urinary tract epithelial carcinoma bacause of the less intraoperative bleeding, minimal invasion, quicker recovery and shorter postoperative hospital stay[7][8][9][10][11].At present there are many surgical approaches for laparoscopic nephroureterectomy. The most common method was the Bishoff method[12], that is, laparoscopic renal and upper ureter resection in the upper abdomen, and lower ureter and partial bladder incision in the lower abdomen.…”
mentioning
confidence: 99%